2017
DOI: 10.17755/esosder.306900
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenleri̇n Pozi̇ti̇f Psi̇koloji̇k Sermayeleri̇ne İli̇şki̇n Algilarinin İncelenmesi̇

Abstract: ÖzPozitif psikolojik sermaye, temellerini pozitif psikoloji ve pozitif örgütsel davranış yaklaşımlarından alan, çalışan verimliliğinin artışına olumlu yönde etki edecek bir dizi nitelik olarak tanımlanan sermaye türüdür. Pozitif psikolojik sermayenin bileşenleri özgüven, iyimserlik, umut, psikolojik dayanıklılık, güven ve dışadönüklüktür. Pozitif psikolojik sermayenin çalışan verimliliğine ve örgütsel davranışlara etkisi büyüktür. Dolayısıyla öğretmenlerin pozitif psikolojik sermaye algılarının ortaya konması … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
36

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 7 publications
3
11
0
36
Order By: Relevance
“…There were also other studies (Çetin, Yeloğlu and Basım, 2015; Çetin, Hazır and Basım, 2013) concluding that shared leadership predicts the psychological resilience of teachers which is a sub-dimension of positive psychological capital. It was also observed in various other studies (Tösten, 2015;Luthans and Jensen, 2002) shared leadership predicts hope of the teachers which is another sub-dimension of positive psychological capital. In conclusion; it was observed that shared leadership is high at primary and secondary schools, that authorities and responsibilities are shared and that the school culture is adopted and shared.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…There were also other studies (Çetin, Yeloğlu and Basım, 2015; Çetin, Hazır and Basım, 2013) concluding that shared leadership predicts the psychological resilience of teachers which is a sub-dimension of positive psychological capital. It was also observed in various other studies (Tösten, 2015;Luthans and Jensen, 2002) shared leadership predicts hope of the teachers which is another sub-dimension of positive psychological capital. In conclusion; it was observed that shared leadership is high at primary and secondary schools, that authorities and responsibilities are shared and that the school culture is adopted and shared.…”
Section: Discussionsupporting
confidence: 66%
“…A total of 53.5% of the participants of the study were male, whereas 46.5% were female. The distributions of the participants according to age groups were 10.5% between the ages of [20][21][22][23][24][25][26][27][28][29][30]40.3% between the ages of [31][32][33][34][35][36][37][38][39][40]33.5% between the ages of 41-50 and 15.8% 51 and above. The distribution according to the school type was 50.6% primary schools and 49.4% secondary schools.…”
Section: Study Population and Sample Groupmentioning
confidence: 99%
“…Ankete katılan banka çalışanlarının psikolojik sermaye puanı 4,4523 olarak bulunmuştur. Tösten (2015) tarafından öğretmenler üzerinde yapılan çalışmada ise psikolojik sermaye puanı 4,28 olarak bulunmuştur.…”
Section: Faktör Analizleri Ve Güvenilirlik Testleriunclassified
“…Umut, istenen hedeflere giden yollar çizebilme ve kendini bu yolları kullanma konusunda motive edebilme kapasitesi ve bu kapasiteye ilişkin algıdır. (Tösten, 2015), özyeterlilik; eşitli çözüm yolları oluşturmak, amaca yönelik eylemde bulunmak ve amaçları gerçekleştirmede başarılı olmak ilişkin gereken inançtır (Avey, Wernsing ve Luthans, 2008: 53). İyimserlik; olaylara karşı pozitif yaklaşmakla ilgilidir ve iyimser olan bireyler, gelecek için çok fazla endişeli değildirler.…”
Section: Introductionunclassified
“…Araştırma bulgularına bakıldığında beden eğitimi öğretmenlerinin psikolojik sermaye düzeylerinin yüksek olduğu görülmüştür. Literatür incelendiğinde; Li ve He'nin (2011) Erkuş ve Fındıklı (2013), Keser (2013), Boamah ve Laschinger (2015), Tösten (2015) ve Çimen'in (2015) yapmış oldukları çalışmalarda da öğretmenlerin psikolojik sermaye düzeylerinin yüksek çıktığı görülmüştür. Bu çalışmalar, çalışmamızın bulgularını destekler niteliktedir.…”
Section: Discussionunclassified